Perkembangan Pengujian Perundang- Undangan di Mahkamah Konstitusi - Pusat Studi Konstitusi FH Andalas (Jurnal Konstitusi, 2016)
The judiciary is a tools to find justice. The Constitutional Court of Republic of Indonesia (MKRI) who attended after the 1945 amendment also established to  fulfill  the  desires  of  the  justice  seeker.  The  Efforts to comply the sense of justice depends on how the constitutional court judges deciding cases. If the judge of the constitutional court failed to parse the meaning of substantive justice, it found the unfair justice. It’s fair according to the judge verdict, but it was unable to fulfill the desires  of the justice seeker. The step of judges to find the justice known as the concept of judicial activism. And its consisting in constitutional court authority namely as judicial review. Within seven years since the MKRI have been formed, the court has become an institution recognized by the justice seeker through the decisions. In fact, the court not only courageous in deciding the facts of the existing law, but further than that, the court also made a bold reform in its verdict forms.